Heart of hope : a small town romance - Score, Lucy (Naperville, Illinois : Bloom Books, 2017)
"Single mom Bristol Quinn is trying desperately to rediscover happiness after the tragic accident that took her younger sister's life. Older sister Savannah's Christmas wedding seems like the perfect time to invite Hope's heart recipient to meet the Quinns and their extended Hope Falls family. But when her letter goes unanswered, Bristol focuses on trying not to ruin her daughter's peewee ice hockey team's season with her pathetic lack of knowledge. And when sexy stranger Beau scrapes her off the ice and offers to teach her to skate and coach, Bristol hopes her luck is finally turning around. Once Beau gets he first good look at Bristol--saving a life no less--he knows that his future has just changed. Will she forgive him for lying when she finds out his real reason for coming to Hope Falls? When the truth comes out and Beau crashes the wedding, Bristol is determined to ignore him until he disappears again. But this time he's got the whole town on his side helping him orchestrate the Christmas surprises of a lifetime."--
Keywords: Man-woman relationships -- Fiction; Single mothers -- Fiction; Heart -- Transplantation -- Fiction; Christmas fiction; Romance fiction